2018
DOI: 10.1101/485862
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of the m6Am methyltransferase PCIF1 reveals the location and functions of m6Am in the transcriptome

Abstract: mRNAs are regulated by nucleotide modifications that influence their cellular fate. Two of the most abundant modified nucleotides are N 6 -methyladenosine (m 6 A), found within mRNAs, and N 6 ,2'-O-dimethyladenosine (m 6 Am), which is found at the first-transcribed nucleotide. A longstanding challenge has been distinguishing these similar modifications in transcriptome-wide mapping studies. Here we identify and biochemically characterize, PCIF1, the methyltransferase that generates m 6 Am. We find that PCIF1 b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
185
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(194 citation statements)
references
References 54 publications
9
185
0
Order By: Relevance
“…First, m 6 Am is generated by the methylation of Am, which is primarily located in the first nucleotide position adjacent to the m 7 G cap structure of mRNA [3][4][5][6][7] . Second, a unique writer protein, phosphorylated CTD-interacting factor 1, is responsible for generating the m 6 Am modification [61][62][63][64] , whereas a methyltransferase complex comprising METTL3, METTL14, WTAP, and KIAA1429 is involved in the generation of the m 6 A modification [22][23][24][25] . Finally, whereas m 6 A is largely demethylated by ALKBH5 but also by FTO, with a weak preference [29][30][31][32] , m 6 Am is preferentially and specifically demethylated by FTO 29,31,62 .…”
Section: N 6 2′-o-dimethyladenosinementioning
confidence: 99%
See 1 more Smart Citation
“…First, m 6 Am is generated by the methylation of Am, which is primarily located in the first nucleotide position adjacent to the m 7 G cap structure of mRNA [3][4][5][6][7] . Second, a unique writer protein, phosphorylated CTD-interacting factor 1, is responsible for generating the m 6 Am modification [61][62][63][64] , whereas a methyltransferase complex comprising METTL3, METTL14, WTAP, and KIAA1429 is involved in the generation of the m 6 A modification [22][23][24][25] . Finally, whereas m 6 A is largely demethylated by ALKBH5 but also by FTO, with a weak preference [29][30][31][32] , m 6 Am is preferentially and specifically demethylated by FTO 29,31,62 .…”
Section: N 6 2′-o-dimethyladenosinementioning
confidence: 99%
“…Although controversial 63,64 , findings from recent studies have revealed that m 6 Am-initiated mRNAs are in greater abundance and have longer half-lives than mRNAs with Am, Gm, Cm, or Um 31,62 . In vitro decapping experiments have shown that m 6 Am-initiated mRNAs are more resistant to decapping by decapping mRNA 2 (DCP2) 65 , resulting in the increased mRNA stability (Fig.…”
Section: N 6 2′-o-dimethyladenosinementioning
confidence: 99%
“…Protein coding mRNAs and non-coding RNAs (e.g., rRNAs, snRNAs and miRNAs) are extensively modified by chemical modifications , including methylation of the N 6 position of adenosine (m 6 A) 2 . While mRNA internal m 6 A methylation is mediated by METTL3 and METTL14, which are members of the MT-A70 family 2 , N 6 -methylation of cap-adjacent N 6 ,2´-O-dimethyladenosine (m 6 Am) is catalyzed by PCIF1 [3][4][5][6] .…”
Section: Dear Editormentioning
confidence: 99%
“…When this nucleotide is adenosine, it can be further methylated on its N6 position (Keith et al, 1978) to yield, together with the 2 0 -O methyl group, a modification termed m 6 Am. Although this modification is known for many years, the methylating enzyme, PCIF1, has been discovered only very recently by several groups (Akichika et al, 2019;Boulias et al, 2019;Sendinc et al, 2019;Sun et al, 2019). Despite such a remarkably simultaneous identification of the effector protein and the confirmation of its specificity for m 6 Am and not the m 6 A modification, the impact of this modification on translation remains unclear, as the experimental results significantly diverge.…”
Section: The First Transcribed Nucleotide and The Cap Structurementioning
confidence: 99%
“…Accordingly, knock-down of PCIF1 resulted in a significant upregulation of many (% 500) proteins. The third study has employed the CAGE approach to show the actual location of the m 6 Am sites to alternative TSSs (Boulias et al, 2019). Interestingly, the authors identified a substantial amount of m 6 Am deposited downstream of the annotated TSS, sometimes even within CDRs or 3 0 UTRs, possibly indicating pervasive transcription initiation.…”
Section: The First Transcribed Nucleotide and The Cap Structurementioning
confidence: 99%